Analisis Praktik Investasi Sosial Melalui Implementasi Program Enam Pilar LAZISMU - Azraq, Ramdhani; Hadaya, Qonita; Septiani, Mutiara Dwi; Syafril, Muhammad Maulana; Ramadhan, Muhammad Aqsyal; Sampean, Sampean; Kolopaking, Lala M (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the implementation of the six-pillar programs of LAZISMU Bogor City in the context of social investment, as well as to evaluate the strategies, impacts, and challenges involved in their execution. Using a descriptive qualitative approach, data were collected through in-depth interviews with program managers and document analysis of the organization's profile and annual activity reports. The findings indicate that the six pillars education, health, economy, social preaching (dakwah), humanitarian aid, and environment are implemented not merely as direct assistance, but as sustainable community empowerment strategies. Programs such as educational scholarships, healthcare services, entrepreneurship training, and the construction of worship facilities have proven to improve the welfare and socio-economic resilience of beneficiaries. Despite challenges in optimizing certain pillars, such as social preaching and environmental programs, LAZISMU has generally demonstrated participatory, transparent, and strategic implementation. Overall, these programs strengthen social capital, increase public trust in the institution, and reduce dependency on aid. Thus, the social investment model implemented by LAZISMU has proven effective in addressing short-term needs while creating sustainable social impact, and it can serve as a replicable best practice in zakat management based on community empowerment.